Factors Related to Adolescent Behavior towards HIV/AIDS Prevention - Purnamaningrum, Yuliasti Eka; Nugrahawati, Ratyas Ekartika Puspita Candra; Hernayanti, Munica Rita; Vajee, Anne (Kesmas, 2019)
In 2016 Special Region of Yogyakarta was ranked 9th as the province with the highest number of people suffered from HIV/AIDS especially at Sleman regency. Globally, AIDS was the second leading cause of adolescents’s death aged of 10-19 years. The purpose of this study was to find out factors affecting the behaviour of the adolescents towards HIV/AIDS prevention. This research using with cross sectional study design. The sampling technique which used was stratified random sampling resulted in 59 respondents from 11th grade students at SMA Negeri 2 Sleman were selected as sample. Data were collected using questionnaire and analyzed using Chi-Square test and Multiple Logistic Regression. The result showed that most respondents 66,1% had sufficient knowledge. Students who showed supportive attitude was 54,2%. Information obtained were mostly from electronic media. Thirty one students (52,5%) showed a positive behaviour toward HIV/AIDS prevention. Chi-Square test’s result showed that factors significantly related to adolescent’s behaviour toward HIV/AIDS prevention were knowledge and attitude. Variables most affecting was attitude (p-value=0,008; PR=4,4; 95% CI=1,4-13,1).